Hubungan Intensitas Pencahayaan dengan Kelelahan Mata Pekerja Produksi Premix dan Bagging Off PT Japfa Comfeed Indonesia - Mohamad Khilmi; Tri Siwi Agustina; Andrea Thrisiawan Pradhana (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Inadequate workplace lighting can contribute to visual fatigue and reduce worker productivity in industrial settings. This study aimed to analyze the relationship between lighting intensity and subjective eye fatigue among workers in the premix and bagging off production areas of PT Japfa Comfeed Indonesia Plant Margomulyo. This study used a quantitative observational design with a cross-sectional approach. The population consisted of 30 workers, and total sampling was applied. Data were collected using the Visual Fatigue Index (VFI) questionnaire and secondary data on lighting intensity measurements. Data analysis included univariate and bivariate analysis using the coefficient contingency test. The results showed that 90.0% of workers were exposed to lighting intensity below 200 lux, and 53.3% experienced eye fatigue. The analysis indicated a very weak association between lighting intensity and eye fatigue (r = 0.132). Similarly, age, length of work, and years of service also showed very weak relationships with eye fatigue. These findings suggest that although the association is weak, inadequate lighting conditions remain a potential risk factor for eye fatigue and should be addressed to improve occupational health.